Die Psalms in die liturgie met verwysing na Psalm 8 as liedteks - Vos, Casparus Johannes Adam (HTS teologiese studies, 2002)
The Psalms in liturgy with reference to Psalm 8 as hymnThe publishing of “Liedboek van die Kerk” (2001) emphasizes the importance of the psalms for liturgy and hymnology. All 150 psalms in “Liedboek” were versified by TT Cloete. This article considers the bridge function of the psalm, the significance and function of the psalms as an open hymnbook and as an anthology, and the literature types found in the psalms. The structure and form of Psalm 8 are analyzed in greater detail. This analysis leads to a literary evaluation and a musicological appreciation of its versification by Cloete.